Professional self-concept in Nurses working in intensive cares unit in hospitals affiliated to medical sciences universities of Tehran in 2014 - Golestan, Fateme; Ashktorab, Tahereh; Zohari anboohi, Sima; Mohtashami, Jamileh; Salmani, Fatemeh (Advances in Nursing & Midwifery, 2016)
Abstract: Background and aim: Professional self-concept is an individual’s perception of self as a professional person and it affects his/her thinking, role development and professional functions. Among the various professions, some needs to have higher self-concept the nursing profession has a special status in this regard. This issue is more important in nurses working in intensive care units because in addition to high experience and sufficient knowledge, they should have special clinical skills and personality. Therefore, the present study was conducted to determine the nurses’ professional self-concept and its’ dimensions scores in nurses working in intensive care units in hospitals affiliated to medical sciences universities of Tehran in 2014. Materials and methods: The present cross-sectional study was conducted on 205 qualified nurses working in Intensive care units in hospitals affiliated to medical sciences universities of Tehran. Data was collected using a questionnaire which consisted of demographic information and “Nurse Self-Concept Questionnaire” (cowin, 2001), after confirming their validity and reliability. The range of total score was 36-288. The SPSS software version 22 was used to analyze the data. Results: The mean score of professional self-concept was 197/20±23/67. The highest and the lowest score were respectively related to dimensions of communication and nurse general self-concept (self-esteem) with the mean of 41/34±4/93 and 16/23±6/96. Conclusion: however intensive care unit nurses gained relatively high professional self-concept score, but it seems that it was far from ideal. Also nurses working in intensive care unit gained the lowest score from nurse general self-concept dimension that it represented the weakness of nurses in this context. Therefor the necessity of education and preparation of nurses, in order to have higher professional self-concept and self-esteem was felt. Key words: Self-Concept- Nursing- Intensive Cares Unit